The new Russian nationalism : imperialism, ethnicity and authoritarianism 2000-15 - Kolstø, Pål; Blakkisrud, Helge (Edinburgh University Press, 2016)
Follows the transformation of Russian nationalist discourse in the 21st century, from imperialism to ethno-nationalism. Russian nationalism, previously dominated by 'imperial' tendencies - pride in a large, strong and multi-ethnic state able to project its influence abroad - is increasingly focused on ethnic issues. This new ethno-nationalism has come in various guises, like racism and xenophobia, but also in a new intellectual movement of 'national democracy' deliberately seeking to emulate conservative West European nationalism. Russia's annexation of Crimea in 2014 and the subsequent violent conflict in Eastern Ukraine utterly transformed the nationalist discourse in Russia. This book provides an up-to-date survey of Russian nationalism as a political, social and intellectual phenomenon by leading Western and Russian experts in the field of nationalism studies. It includes case studies on migrantophobia; the relationship between nationalism and religion; nationalism in the media; nationalism and national identity in economic policy; nationalism in the strategy of the Putin regime as well as a survey-based study of nationalism in public opinion.